2020
DOI: 10.1186/s12876-020-01296-x
|View full text |Cite
|
Sign up to set email alerts
|

Elderly-onset vs adult-onset ulcerative colitis: a different natural history?

Abstract: Background: Incidence of ulcerative colitis (UC) in elderly population is increasing because of ageing and because of its minimal impact on life span. Data on natural history, outcomes and therapeutic strategies are limited. Our aim is to characterize UC in elderly-onset patients followed at our Inflammatory Bowel Disease outpatient clinic and compare with adult-onset UC. Methods: From January 2000 to June 2019, 94 patients with UC diagnosed after the age of 65 years (elderly group, E-O) were identified and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 39 publications
3
23
2
1
Order By: Relevance
“…Second, we did not collect data on the comorbidities including malignancies and infections that may affect UC outcomes in this study. However, unlike the previous studies that reported a worse prognosis of EOUC than of N-EOUC, 12 - 14 the results of the present study may suggest that EOUC does not have an aggressive disease course compared to that of N-EOUC despite the possibility of a higher burden of comorbidities in patients with EOUC than in those with N-EOUC. Third, whether the findings of this study can be generalized to other Asian populations remains unclear, considering that there are genotypic and phenotypical variations in IBD among Asian countries.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Second, we did not collect data on the comorbidities including malignancies and infections that may affect UC outcomes in this study. However, unlike the previous studies that reported a worse prognosis of EOUC than of N-EOUC, 12 - 14 the results of the present study may suggest that EOUC does not have an aggressive disease course compared to that of N-EOUC despite the possibility of a higher burden of comorbidities in patients with EOUC than in those with N-EOUC. Third, whether the findings of this study can be generalized to other Asian populations remains unclear, considering that there are genotypic and phenotypical variations in IBD among Asian countries.…”
Section: Discussioncontrasting
confidence: 99%
“… 7 , 17 , 19 , 25 Meanwhile, referral center-based studies from both Western and Eastern countries showed higher cumulative rates of colectomy in the EOUC group than in the N-EOUC group. 12 - 14 Also, recent multicenter studies from Hong Kong showed that EO-IBD patients had a higher risk of infection, cancer, and hospitalization. 15 , 16 Although the cause of this discrepancies among results is unclear, differences in the study design (referral center-based vs population-based) may play a critical role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that elderly UC patients were more likely to be male and less likely to have a family history of inflammatory bowel disease (IBD) or extraintestinal manifestations 10,11 . Similar to the symptoms in younger patients, older UC patients typically present abdominal pain, fecal urgency, and bloody diarrhea, and there are no significant changes in symptomatic severities between the two groups 12 .…”
Section: Clinical Presentation In Elderly Ulcerative Colitismentioning
confidence: 99%
“…Using a well-controlled model of experimental systemic inflammation and multiorgan injury triggered by controlled administration of gut-damaging chemical dextran sulfate sodium (DSS), we, in this study, examined the effect of preconditioning with subclinical endotoxemia on the priming of neutrophils in vivo as well as the development of systemic inflammation and multiorgan damage. Previous studies suggest that pre-existing conditions such as obesity and aging increase the risk for more severe ulcerative colitis as well as subsequent comorbidity risks, including sepsis ( 10 12 ). Subclinical endotoxemia manifests in humans with obesity and ageing ( 13 15 ), which may precondition innate immune system for aggravated systemic inflammation and organ damage following subsequent ulcerative colitic injury.…”
Section: Introductionmentioning
confidence: 99%